Magnetic stimulus responsive vancomycin drug delivery system based on chitosan microbeads embedded with magnetic nanoparticles. Issue 6 (20th October 2017) - Mohapatra, Ankita; Harris, Michael A.; LeVine, David; Ghimire, Madhav; Jennings, Jessica A.; Morshed, Bashir I.; Haggard, Warren O.; Bumgardner, Joel D.; Mishra, Sanjay R.; Fujiwara, Tomoko
Abstract: Local antibiotic delivery can overcome some of the shortcomings of systemic therapy, such as low local concentrations and delivery to avascular sites. A localized drug delivery system (DDS), ideally, could also use external stimuli to modulate the normal drug release profile from the DDS to provide efficacious drug administration and flexibility to healthcare providers. To achieve this objective, chitosan microbeads embedded with magnetic nanoparticles were loaded with the antibiotic vancomycin and stimulated by a high frequency alternating magnetic field. Three such stimulation sessions separated by 1.5 h were applied to each test sample. The chromatographic analysis of the supernatant from these stimulated samples showed more than approximately 200% higher release of vancomycin from the DDS after the stimulation periods compared to nonstimulated samples. A 16‐day long term elution study was also conducted where the DDS was allowed to elute drug through normal diffusion over a period of 11 days and stimulated on day 12 and day 15, when vancomycin level had dropped below therapeutic levels. Magnetic stimulation boosted elution of test groups above minimum inhibitory concentration (MIC), as compared to control groups (with no stimulation) which remained below MIC. The drug release from test groups in the intervals where no stimulation was given showed similar elution behavior to control groups. These results indicate promising possibilities of controlled drug release using magnetic excitation from a biopolymer‐based DDS. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2169–2176, 2018.